Capsaicinoids reduce the viability of a norovirus surrogate during kimchi fermentation. (November 2019) - Lee, Hee-Min; Kim, Su-Ji; Lee, Jae Yong; Park, Boyeon; Yang, Ji-Su; Ha, Sang-Do; Choi, Changsun; Ha, Ji-Hyoung
Abstract: The present study investigated the survival of murine norovirus (MNV) during the fermentation of cabbage kimchi and baek kimchi at different temperatures. Changes in MNV titer, lactic acid bacteria (LAB) count, capsaicinoid and organic acid content, pH, salinity, and acidity were measured for 6 weeks. MNV titer was reduced to a greater degree during storage at 10 °C (P < 0.01) than at 4 °C. The reduction in titer was also greater for cabbage kimchi (1.57 ± 0.12 log10  PFU/g) than for baek kimchi (0.61 ± 0.13 log10  PFU/g). LAB, capsaicin (CAP), dihydroCAP, lactic acid, acetic acid, and acidity were negatively correlated, whereas pH was positively correlated with MNV titer for both types of kimchi during fermentation. Moreover, CAP levels strongly correlated with MNV titer at 4 °C (−0.973) and 10 °C (−0.969). Thus, the presence of CAP could inhibit MNV survival during kimchi fermentation. Highlights: MNV viability during kimchi fermentation at different temperatures was investigated. A greater reduction was observed in MNV titers during storage at 10 °C than at 4 °C. The decrease in MNV titer was greater for cabbage kimchi than for baek kimchi. Capsaicin level was highly correlated with MNV titer at 4 °C and 10 °C.